Challenges to implementing parent‐focused antibullying policies: Lessons learned in Connecticut. Issue 8 (7th May 2022) - Martinez, Andrew; O'Connor, Kelly; McMahon, Susan; Bhatia, Shaun; Primavera, Judy
Abstract: Bullying is a public health concern warranting policy‐level responses. Toward this end, states are enacting antibullying policies that require schools to be inclusive of parents. The current study examines parent‐related challenges as schools implement newly amended antibullying legislation in Connecticut. School personnel data were analyzed from 24 semistructured interviews and qualitative survey responses across 300 schools. We used inductive coding techniques to synthesize data into broader themes. Four major challenges to implementing antibullying policies emerged from qualitative analysis: (1) challenges to parent engagement, (2) interpretation of the word "bullying, " (3) parent affective responses, and (4) conflicting home and school norms. State antibullying laws call for greater parent engagement, but schools are often not fully inclusive of parents. A greater focus on the developing a positive school climate and a culture of parental engagement can facilitate the implementation of antibullying laws and ensure the safety of children. Highlights: State antibullying laws have increasingly included requirements that leverage the role of parents and guardians. Four challenges to implementation are noted in Connecticut. Developing a positive school climate and a culture of parental engagement may facilitate the implementation of state antibullying laws.